Using social media as a cost‐effective resource in the photo‐identification of a coastal bottlenose dolphin community. Issue 8 (5th June 2020) - Gibson, Catherine Elizabeth; Williams, David; Dunlop, Rebecca; Beck, Suzanne
Abstract: Bottlenose dolphins encountered around the Irish coast are considered part of a wide‐ranging coastal community; however, knowledge on the significance of the north of Ireland for this species is limited by a lack of dedicated effort. Through social media, the opportunity now exists to gather large volumes of citizen science data in the form of high‐quality images, potentially extending the spatial and temporal scope of photo‐identification studies. The purpose of this study was to investigate social media as a data resource for photo‐identification studies and to provide a preliminary assessment of bottlenose dolphins in the north of Ireland. Specifically, the study sought to examine the photo‐identification data for spatial clustering. The study identified 54 well‐marked individuals and provided evidence of potential year‐round occurrence, with successful re‐sightings throughout the study period (2007–2016). There was a geographic concentration of re‐sightings along the north of Ireland, suggestive of interannual site fidelity. These results provide scientific rationale for strategically targeting the north of Ireland in future research on the Irish coastal community. For effective conservation of the bottlenose dolphin it is imperative that scientific research, and resultant management objectives, consider wide‐ranging communities such as the Irish coastal community. Our research highlights data collection via social media as a cost‐effective and scientifically valuable tool in the photo‐identification of coastal cetaceans. We recommend that this method is used in research on low‐density and wide‐ranging coastal cetaceans.